Population and spatial ecology of horseshoe crabs (Limulidae) in a nursery ground at Pulau Bedukang, Brunei Bay, Borneo - AHMAD FAHMI ROZAINI; KEVIN H. LAURIE; DAVID J. MARSHALL (Society for Indonesian Biodiversity, 2023)
Abstract. Rozaini AF, Laurie KH, Marshall DJ. 2023. Population and spatial ecology of horseshoe crabs (Limulidae) in a nursery ground at Pulau Bedukang, Brunei Bay, Borneo. Biodiversitas 24: 4485-4492. Suitable nursery habitat to support populations of juvenile horseshoe crabs is becoming threatened globally. There are currently no formal studies on juvenile populations of the horseshoe crabs (Limulidae) for Brunei Darussalam (Brunei, Borneo). We investigated body size structure, population cohort and ecological distribution of juvenile horseshoe crabs associated with a mudflat on Pulau Bedukang, in Brunei Bay. Seventy juveniles were retrieved during four sampling days covering two seasons and four study sites. Carcinoscorpius rotundicauda and Tachypleus gigas were common, whereas only two individuals of Tachypleus tridentatus were found. Carapace width (size) was similar in the common species and there was no difference in juvenile size between the seasons and study sites. Body weight to carapace width relationships showed that the species grew at similar rates, although C. rotundicauda developed faster, producing 14 compared to the eight pre-migration mudflat instars produced by T. gigas. Species densities were similar, and there was no spatial separation of species or juvenile size across the mudflat or in relation to the mangrove forest edge. Nearest-neighbor (NN) analysis showed that individual crabs were generally dispersed. Their mudflat cohabitation suggests physiological and behavioral plesiomorphies for common optimal developmental salinity and temperature conditions. This study provides baseline information for comparison with other regional studies and for local conservation planning.